2018
DOI: 10.1111/cup.13372
|View full text |Cite
|
Sign up to set email alerts
|

The expression of terminal deoxynucleotidyl transferase and paired box gene 5 in Merkel cell carcinomas and its relation to the presence of Merkel cell polyomavirus DNA

Abstract: Background Merkel cell carcinoma (MCC) tumor samples frequently express B‐lymphoid lineage markers. However, the reasons for expression of specific B‐lymphoid lineage markers are still unclear. We studied the expression of TdT and PAX5 (two B‐cell lymphoid lineage markers) in a large pool of MCC tissue microarray samples. Methods Immunoexpression and staining intensities of TdT and Pax‐5 were statistically correlated with patient, tumor, Merkel cell polyomavirus (MCV), and disease‐specific parameters. Results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 50 publications
0
7
0
Order By: Relevance
“…In addition, the coexpression of terminal deoxy nucleotidyl transferase (TdT), paired box 5 (Pax5) and immunoglobulin chains, all markers expressed during B-cell differentiation, has been observed in MCC tumors (62, 64). Initially, the frequency of TdT and Pax5 positivity was reported to be about 65% ( N = 187) and 90% ( N = 143) of MCC cases (64); however, recently observed rates were lower, 26% ( N = 217) or 23% ( N = 213) (15, 63). Of note, expression of immunoglobulin chains was restricted to the MCPyV(+) subset and detected in about 70% of cases (65).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the coexpression of terminal deoxy nucleotidyl transferase (TdT), paired box 5 (Pax5) and immunoglobulin chains, all markers expressed during B-cell differentiation, has been observed in MCC tumors (62, 64). Initially, the frequency of TdT and Pax5 positivity was reported to be about 65% ( N = 187) and 90% ( N = 143) of MCC cases (64); however, recently observed rates were lower, 26% ( N = 217) or 23% ( N = 213) (15, 63). Of note, expression of immunoglobulin chains was restricted to the MCPyV(+) subset and detected in about 70% of cases (65).…”
Section: Introductionmentioning
confidence: 99%
“…In 2013, it was first proposed by zur Hausen and colleagues that pre/pro B cells are the origin cell of MCC, given that MCC expresses both terminal deoxynucleotidyl transferase (TdT) and paired box protein 5 (PAX5, the coexpression of which is only normally seen in B cells) and immunoglobulin [ 96 ]. Subsequent studies confirmed that the presence of B cell markers is positively correlated with MCPyV-positive status in MCC tumors [ 106 , 107 ]. The major questions underlying this hypothesis are whether MCPyV infects pre/pro B cells inside the dermis and whether these cells enter the dermis before or during oncogenesis.…”
Section: Cell Of Origin For MCCmentioning
confidence: 89%
“…1,7 Besides, terminal deoxynucleotidyl transferase immuno-histo-staining can strengthen MCC diagnosis. 8 The recommended treatment for MCC is wide local excision with a healthy margin of 1-3 cm with adjacent therapies. Studies showed that MCC has a local recurrence, local lymph node metastasis, and distant metastasis rates of 20%-75%, 31%-80%, and 26%-75%, respectively.…”
Section: Discussionmentioning
confidence: 99%